MUHAMMAD IBN ‘ABD AL-WAHHÂB DAN GERAKAN WAHABI - Mangasing, Mansur (State Institute of Islamic Studies (IAIN) Palu, 2008)
In the Islamic world, in the middle age, the ideas on reformation and the efforts of purification of akîdah had emerged. This was a reaction against the extant political condition and tauhid comprehension of Muslims. In Arab, a chief figure, Muhammad ibn ‘Abd al-Wahhâb who possessed a great concern towards the matter of akîdah purification of Muslims and Islamic reformation, emerged. The efforts of al-Wahhâb finally developed into a movement called the Wahabiyyah Movement. The main target of this movement was to purify Muslims’ akîdah that had been mixed with heretics. Kata Kunci: Muhammad ibn ‘Abd al-Wahhâb, Gerakan Wahabi, pemurnian Islam, pembaruan Islam